Perbedaan Warna Cahaya Lampu Terhadap Performa Cacing Tanah (Lumbricus rubellus) - V. A. Mendrofa; A. M. Fuah; Winarno; B. K. Sheehan; E. A. Syahrin (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2022)
Earthworms are nocturnal animals and have negative phototaxis, therefore the presence and color of light are thought to affect the performance of this Lumbricus rubellus earthworm. This study aims to analyze the effect of different color lights on Lumbricus rubellus performance. This study used acompletely randomized design (RAL), six color treatments (red, orange, yellow, green, blue, and purple, and dark as a control) and three replications with variables observed were weight gain, media weight, number of segments to the clitellum, and the number of cocoons. The results showed that the six types of color had different effects on the performance of the earthworm Lumbricus rubellus. The red color lights had a better effect on the weight of the earthworm, the number of cocoons and the number of segments compared to other colors, while the yellow color had a lower effect.